Age structure of amphibian populations with endemic chytridiomycosis, across climatic regions with markedly different infection risk. Issue 7 (24th July 2022) - Turner, Anna; Heard, Geoffrey; Hall, Andrew; Wassens, Skye
Abstract: Threatening processes, such as disease, can drive major changes in population demographics of the host. Chytridiomycosis, caused by the fungal pathogen Batrachochytrium dendrobatidis ( Bd ), has led to the decline of at least 500 amphibian species across the globe and has been shown to truncate host age structure by lowering adult survival rates. This results in heavy reliance on annual recruitment and the inability to recover in the event of periodic recruitment failure. We used skeletochronology to determine the age structure, growth, and survival rates of populations of an endangered amphibian, Litoria raniformis, with endemic chytridiomycosis, across two climatically disparate regions in south‐eastern Australia: semi‐arid and temperate. Contrary to predictions, populations in the semi‐arid region (in which chytrid prevalence is substantially lower due to high temperatures) displayed a more truncated age structure than populations in the temperate study regions. Maximum recorded age was only two years in the semi‐arid region compared with up to four years in the temperate region. Wetland hydroperiod and average seasonal air temperature were correlated with age, and males had a slightly higher survival rate than females (0.31 for males and 0.27 for females). Despite the previously documented differences in chytrid prevalence between the two climatic regions, water availability and wetland hydroperiods appear the over‐riding determinants of the age structure and survival rates of L. raniformis . Targeted management which ensures water availability and improves survival of 1‐year‐old frogs into their second and third breeding season would reduce the impact of stochastic events on L. raniformis, and this may be true for numerous frog species susceptible to chytridiomycosis. Abstract : Populations of a chytrid‐infected amphibians, Litoria raniformis, are dominated by relatively young individuals at both the semi‐arid and temperate extent of their range. Hydroperiod and average seasonal air temperature are key environmental drivers of age and survival rates.